Ge-on-Si avalanche photodiodes with photon trapping nanostructures for sensing and optical quantum applications - Wu, Shaoteng (2023)
High-sensitivity Ge/Si avalanche photodiodes (APDs) have recently gained attention for their application in sensing and optical communication due to their low cost and CMOS compatible process. However, compared to commercial III–V compound APDs, Ge/Si APDs usually suffer from the issue of relatively low primary responsivity. In this paper, we report Ge-on-Si separate absorption, charge, and multiplication avalanche photodiodes (SACM-APDs) with photon-trapping nanostructures to enhance light absorption. Besides, by optimizing the depth of the holes, the photon trapping structure could reduce the dark current without compromising the avalanche effect as confirmed by both simulations and experimental results. As a result, the responsivity of the photon trapping APDs increases by 20-50 % from that of control APDs at the 1,550 nm wavelength band. Furthermore, a quantum efficiency higher than 80% could be achieved at 1550 nm when the photon trapping Ge-on-Si APD is on Si-on-insulator (SOI) platforms as predicted by simulations. Our results demonstrate that the photon trapping Ge/Si APDs exhibit superior dark current, light absorption and gain than those of the control devices, which have the potential applications in sensing and optical quantum communications.